Deprescribing practices, habits and attitudes of geriatricians and geriatricians-in-training across Europe: a large web-based survey - van Poelgeest, Eveline P; Seppala, Lotta J; Lee, Jihoo M; Bahat, Gülistan; Ilhan, Birkan; Lavan, Amanda H; Mair, Alpana; van Marum, Rob J; Onder, Graziano; Ryg, Jesper; Fernandes, Marília Andreia; Garfinkel, Doron; et al. (European geriatric medicine, 2022)
PURPOSE: To provide an overview of the current deprescribing attitudes, practices, and approaches of geriatricians and geriatricians-in-training across Europe. METHODS: An online survey was disseminated among European geriatricians and geriatricians-in-training. The survey comprised Likert scale and multiple-choice questions on deprescribing approaches and practices, deprescribing education and knowledge, and facilitators/barriers of deprescribing. Responses to the survey questions and participant characteristics were quantified and differences evaluated between geriatricians and geriatricians-in-training and between European regions. RESULTS: The 964 respondents (median age 42 years old; 64% female; 21% geriatricians-in-training) were generally willing to deprescribe (98%) and felt confident about deprescribing (85%). Despite differences across European regions, the most commonly reported reasons for deprescribing were functional impairment and occurrence of adverse drug reactions. The most important barriers for deprescribing were patients' unwillingness, fear of negative consequences, lack of time, and poor communication between multiple prescribers. Perceived risk of adverse drug reactions was highest for psychotropic drugs, nonsteroidal anti-inflammatory drugs, cardiovascular drugs, and opioid analgesics. Only one in four respondents (23% of geriatricians and 37% of geriatricians-in-training) think education in medical school had sufficiently prepared them for deprescribing in clinical practice. They reported that their future deprescribing activities would probably increase with improved information sharing between various prescribers, deprescribing recommendations in guidelines, and increased education and training. Approximately 90% think that a paradigm shift is required for prescribers and patients, increasing focus on the possible benefits of deprescribing (potentially) inappropriate medications. CONCLUSIONS: Based on the outcomes of this survey, we recommend investing in improved inter-professional communication, better education and evidence-based recommendations to improve future patient-centered deprescribing practices.
Keywords: internet; Online survey; geriatři; průzkumy a dotazníky; Deprescriptions; mužské pohlaví; Internet; zvyky; depreskripce; Habits; Geriatric medicine; Medication review; ženské pohlaví; Deprescribing; Humans; Surveys and Questionnaires; Geriatricians; Older adults; nežádoucí účinky léčiv; Female; Drug-Related Side Effects and Adverse Reactions; lidé; Male; Adverse drug effects